The perception of youth reluctancy to register as voters in Malaysia: a case study in UiTM Seremban / Nor Nadzirah Syazwani Mohd Khair and Wan Nur Azreen Azhar - Mohd Khair, Nor Nadzirah Syazwani; Azhar, Wan Nur Azreen (2022)
This study emphasizes the perception of youth reluctancy to register as voters in Malaysia. Youths are frequently referred to as our "future leaders'' and are considered a glimmer of hope in situations of competing ideas and viewpoints, particularly in politics. Besides, youth actually hold a very large amount of influence when it comes to elections if more youth participate in the election as the population of youth accounted for 46.64% of the whole population. However, according to Deputy Minister in the Prime Minister Department, about 4.2 million people were above 21 years old and still not yet registered as voters and the figure represented 22% of the total number of Malaysians currently eligible to vote. Therefore, the study is aimed to identify the perception of youth reluctancy to register as voters among students at UiTM Seremban Campus. This study uses the population of students from UiTM Seremban, and the number of samples proposed is 357 people. Surveys through questionnaires were used to collect research data and it was virtually distributed to respondents. In order to see the reluctance of youth to register as voters, the main determinants use in this study were educational level, peer influence, SPR policy, and political condition. This research found that the reluctance of youth to register as voters among the UiTM Seremban students can be considered as high. In addition, the study also found that the educational level, peer influence, and SPR policy do contribute to the perception of youth reluctancy to register as voters. However, the political condition did not show any correlation. Therefore, from this research, it is hoped that it could be used by stakeholders to assist them to have insight into the reaction or stance of youth with regard to registering as voters.